2009
DOI: 10.1677/jme-09-0071
|View full text |Cite
|
Sign up to set email alerts
|

Visfatin regulates insulin secretion, insulin receptor signalling and mRNA expression of diabetes-related genes in mouse pancreatic β-cells

Abstract: The role of the adipocyte-derived factor visfatin in metabolism remains controversial, although some pancreatic b-cellspecific effects have been reported. This study investigated the effects of visfatin upon insulin secretion, insulin receptor activation and mRNA expression of key diabetes-related genes in clonal mouse pancreatic b-cells. b-TC6 cells were cultured in RPMI 1640 and were subsequently treated with recombinant visfatin. One-hour static insulin secretion was measured by ELISA. Phospho-specific ELIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
65
1
2

Year Published

2011
2011
2015
2015

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(72 citation statements)
references
References 23 publications
(25 reference statements)
4
65
1
2
Order By: Relevance
“…However, its operative molecular mechanism is not fully elucidated [35]. Visfatin regulates insulin secretion, insulin receptor signaling, and mRNA expression of diabetes-related genes in mouse pancreatic beta-cells [36]. Visfatin (NAMPT)-mediated systemic nicotinamide adenine dinucleotide (NAD) biosynthesis could alter the enzymatic activities of NAD-dependent deacetylase Sirt1 and affect important metabolic pathways that are essential for regulating glucose-stimulated insulin secretion in pancreatic beta cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, its operative molecular mechanism is not fully elucidated [35]. Visfatin regulates insulin secretion, insulin receptor signaling, and mRNA expression of diabetes-related genes in mouse pancreatic beta-cells [36]. Visfatin (NAMPT)-mediated systemic nicotinamide adenine dinucleotide (NAD) biosynthesis could alter the enzymatic activities of NAD-dependent deacetylase Sirt1 and affect important metabolic pathways that are essential for regulating glucose-stimulated insulin secretion in pancreatic beta cells [37].…”
Section: Discussionmentioning
confidence: 99%
“…Visfatin shows some insulin mimetic properties [24], and its molecular mechanism of actions is under vigorous challenge [4,24,25]. Recently, Brown et al [26] suggested that visfatin can significantly regulate insulin secretion, insulin receptor phosphorylation, and intracellular signaling and expression of a number of beta cell function-associated genes in mouse beta cells.…”
Section: Discussionmentioning
confidence: 99%
“…5 Moreover, it seems to be involved in the regulation of insulin secretion and receptor signaling. 17 Plasma visfatin concentration correlates strongly with the amount of visceral fat. 5 Data on mice have shown that plasma levels of this adipokine increase in the obese state and in mice consuming high fat diet.…”
Section: Introductionmentioning
confidence: 99%